Pengaruh Model Pembelajaran Kooperatif Tipe Number Heads Together (NHT) Terhadap Hasil Belajar Sejarah - Eka Sari Handayani (Jurnal Pendidikan Sejarah, 2016)
This research aims to determine the effect of cooperative learning model type Numbered Head Together (NHT) toward learning history outcomes at SMA Negeri 3 Kabupaten Tangerang. This research is quantitative approach with experimental method. From the result of statistical calculation, it can be concluded that there is a significant effect in cooperative learning model type Numbered Head Together (NHT) toward learning history outcomes which come out from tcount value 5,961 >ttable 2,00 with significant rate 0,05.